Na fundamencie braku. "Ghetto potępione" czytane na nowo - Halina Magiera (Fabrica Litterarum Polono-Italica, 2019)
The paper is an attempt to analyse and interpret one of Kazimiera Alberti’s novel, The Decried Ghetto / Ghetto potępione, using new theoretical tools and methodology, i.a. Derrida’s deconstruction and feminist approach. The novel’s main character, Róża Grünszpann, not only torments herself with self-reproach and her own prejudices towards ethnic group, she came from – she also struggles with gender perception. These three factors are inseparably connected. Hence, Róża – by helping people from her childhood home, the ghetto – tries to manage her own fears, repulsion and identity issues.